Limnological characteristics of Missouri reservoirs: synthesis of a long-term assessment. (1st October 2020) - Jones, John R.; Thorpe, Anthony P.; Obrecht, Daniel V.
Abstract: Jones JR, Thorpe AP, Obrecht DV. 2020. Limnological characteristics of Missouri reservoirs: synthesis of a long-term assessment. Lake Reserv Manage. 36:412–422. Missouri reservoirs reflect their edaphic location in the midcontinent ecotone between historic prairies and forests. Most are small (median surface area of 28 ha) but provide essential services in a region with few natural lakes. Long-term summer monitoring data (1978–2016) show that they span the full trophic state range, with oligotrophic reservoirs in deep, forested valleys and eutrophic–hypereutrophic impoundments in agricultural regions. In regression analysis, row crop (a surrogate for agricultural nutrient loss) along with depth and flushing rate accounted for some two-thirds of variation among reservoir nutrients. Hydrology is a strong influence; total phosphorus (TP) effectively doubles between flushing rates of 0.25/yr and 2/yr when holding land cover and depth constant. Temporal variation characterizes these impoundments; many show >3-fold range in mean summer trophic state metrics, which is influenced by the volume and timing of annual inflow. This variation may mask gradual nutrient-driven changes in trophic state; based on simulation, doubling chlorophyll (Chl) in a given lake over 20 yr could be undetectable with routine summer monitoring. Some two-thirds of cross-system variation in mean Chl was explained by TP, and inorganic solids further reduced variation (negative coefficient). On average, Chl:TP ratios increased from 0.28 to 0.48 during summer, coincident with a decline in inorganic solids. Inorganic particulates largely determine Secchi transparency and can result in light limitation of phytoplankton. Small reservoirs cover nearly double the area of major impoundments worldwide and are known for an intensity of ecological processes, making this information relevant beyond the region.